Tumor necrosis and infiltrating macrophages predict survival after curative resection for cholangiocarcinoma. (3rd August 2017) - Atanasov, Georgi; Dietel, Corinna; Feldbrügge, Linda; Benzing, Christian; Krenzien, Felix; Brandl, Andreas; Mann, Elli; Englisch, Julianna Paulina; Schierle, Katrin; Robson, Simon C.; Splith, Katrin; Morgul, Mehmet Haluk; et al.
ABSTRACT: Background . Tumor necrosis as well as tumor-associated macrophages (TAMs) in the tumor invasive front (TIF) have been suggested to have a prognostic value in selected solid tumors, inclusive hilar cholangiocarcinoma. However, little is known regarding their influence on tumor progression and prognosis in intrahepatic cholangiocarcinoma (iCC). Methods . We analyzed surgically resected tumor specimens of human iCC (n = 88) for distribution and localization of TAMs, as defined by expression of CD68, formation of necrosis and extent of peritumoral fibrosis. Abundance of TAMs, tumor necrosis and grade of fibrosis were assessed immunohistochemically and histologically and correlated with clinicopathological characteristics, tumor recurrence and patients' survival. Statistical analysis was performed using SPSS software. Results . Patients with tumors characterized by low levels of TAMs in TIF or necrosis showed a significantly decreased 1-, 3- and 5-y recurrence-free survival and a significantly decreased overall survival, when compared with patients with tumors showing high levels of TAMs in TIF or no necrosis. Patients with high density of TAMs in TIF showed significantly lower incidence of tumor recurrence, as well ( p < 0.05). Absence of tumor necrosis and TAMs in TIF were confirmed as independent prognostic variables in the multivariate survival analysis (all p < 0.05). Conclusions . High levels of TAMs in TIF or absence of histologic tumor necrosis are associated with a significantly improved recurrence-free and overall survival of patients with iCC. These results suggest TAMs and necrosis as valuable prognostic markers in routine histopathologic evaluation, and might indicate more individualized therapeutic strategies.